2018
DOI: 10.1038/s41598-018-35424-1
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-induced supercurrent through topological insulator based nanowires for quantum computation studies

Abstract: Proximity-induced superconducting energy gap in the surface states of topological insulators has been predicted to host the much wanted Majorana fermions for fault-tolerant quantum computation. Recent theoretically proposed architectures for topological quantum computation via Majoranas are based on large networks of Kitaev’s one-dimensional quantum wires, which pose a huge experimental challenge in terms of scalability of the current single nanowire based devices. Here, we address this problem by realizing ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Interestingly, W-C deposits have been applied to the editing of superconducting circuits based on other superconductors [94]. • W-C FIBID deposits have been frequently used to induce superconductivity by proximity effect on other materials such as graphene [95], bismuth [96,97], copper and cobalt [98], gold [99] and Bi 2 Se 3 [100]. In the last case, topological superconductivity was searched for Majorana-based quantum computing applications.…”
Section: Direct Growth Of Superconducting Devices By Focused Electron...mentioning
confidence: 99%
“…Interestingly, W-C deposits have been applied to the editing of superconducting circuits based on other superconductors [94]. • W-C FIBID deposits have been frequently used to induce superconductivity by proximity effect on other materials such as graphene [95], bismuth [96,97], copper and cobalt [98], gold [99] and Bi 2 Se 3 [100]. In the last case, topological superconductivity was searched for Majorana-based quantum computing applications.…”
Section: Direct Growth Of Superconducting Devices By Focused Electron...mentioning
confidence: 99%
“…Topological surface states of Bi 2 Se 3 possess helical Dirac dispersion with spin locked to momentum, which makes it potentially promising for quantum computing spintronics applications ( Bhattacharyya et al., 2018a , 2018b ; He et al., 2019 ; Khokhriakov et al., 2020 ). Numerous studies have demonstrated that topological surface states of topological insulators exhibit novel electronic responses and fascinating optoelectronic effects to polarized light ( Besbas et al, 2016 ; Kastl et al., 2015 ; Wang et al., 2019a , 2019b , 2019c ; Zhuang et al., 2021 ).…”
Section: Optoelectronic Applications Of 2d Bi 2 Se 3 Materialsmentioning
confidence: 99%
“…In addition, Bi 2 Se 3 demonstrates attractive optoelectronic properties such as broadband optical absorption ( Guo et al., 2013 ; Peng et al., 2012 ; Yao et al., 2014 ), thickness-dependent surface bandgap ( He et al., 2010 ; Post et al., 2013 ) and polarization-sensitive photocurrent ( Besbas et al, 2016 ; Duan et al., 2014 ; Yan et al., 2014 ). These intriguing properties are favorable for Bi 2 Se 3 as a promising candidate for optoelectronic devices ( Bhattacharyya et al., 2018a , 2018b ; Sharma et al., 2016 ; Wang et al., 2019a , 2019b , 2019c ; Zhang et al., 2010 ). Up to now, a large amount of efforts have been devoted and significant progress have been made in the study of 2D Bi 2 Se 3 from materials preparation to optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The closure of QMT experiment in principle needed the measurement of current with an uncertainty better than 1 part in 10 8 . CSIR-NPL maintains primary quantum standards of voltage and resistance through programmable Josephson voltage standard and quantum Hall resistance standard, and efforts are targeted for development of the quantum current standard [88,89].…”
Section: Status Of Unit Of Current (Ampere)mentioning
confidence: 99%